204k views
4 votes
Enter the statement, with the values in the same order, but with parentheses so that the statement is true. 6 × 3 − 4 × 3 + 16 ÷ 4 = 11

User Lou Bagel
by
5.8k points

1 Answer

3 votes

Answer:

The correct statement with parenthesis is (6 × 3) − ((4 × 3 )+ 16) ÷ 4 = 11

Explanation:

The statement with parenthesis

(6 × 3) − ((4 × 3 )+ 16) ÷ 4 = 11

On solving we will get

18 - (28÷ 4)

18-7

11

Hence, the correct statement with parenthesis is (6 × 3) − ((4 × 3 )+ 16) ÷ 4 = 11

User Sutee
by
5.3k points